EFEKTIVITAS PROSES MEDIASI DALAM MENGURANGI PERKARA PERCERAIAN DITINJAU DARI PERMA NOMOR 01 TAHUN 2016 TENTANG PEDOMAN MEDIASI DI PENGADILAN (Studi Kasus di Pengadilan Negeri Singaraja) - dewi, Ni Ketut Dessy Fitri yanti; Lasmawan, I Wayan; Dantes, Komang Febrinayanti (Universitas Pendidikan Ganesha, 2024)
This examination makes sense of exhaustively the adequacy of the intercession cycle in decreasing separation cases as far as PERMA Number 01 of 2016 concerning Rules for Intercession in Court. The point of this exploration is to examine whether PERMA Number 01 of 2016 is viable in decreasing separation cases through the intervention cycle at the Singaraja Locale Court. The sort of examination utilized is an exact juridical exploration with distinct exploration attributes. The Singaraja District Court served as the setting for this investigation. The information assortment methods utilized were record concentrate on strategies, perception, and meetings. Subjective information handling and investigation strategies. The examination results show that the execution of the intervention cycle is as per PERMA, notwithstanding, the outcomes, the achievement pace of intercession is still exceptionally low. The litigants' failure to attend the mediation process is typically to blame for mediation failures at the Singaraja District Court. So it is important to understand the disputants that the intervention cycle is vital, particularly in separate cases.